# Prove by method of induction, for all n ∈ N: 1.2 + 2.3 + 3.4 + ..... + n(n + 1) = n3(n+1)(n+2) - Mathematics and Statistics

Sum

Prove by method of induction, for all n ∈ N:

1.2 + 2.3 + 3.4 + ..... + n(n + 1) = "n"/3 ("n" + 1)("n" + 2)

#### Solution

Let P(n) ≡ 1.2 + 2.3 + 3.4 + ..... + n(n + 1) = "n"/3 ("n" + 1)("n" + 2), for all n ∈ N

Step 1:

For n = 1

L.H.S. = 1.2 = 2

R.H.S. = 1/3(1 + 1)(1 + 2) = 2

∴ L.H.S. = R.H.S. for n = 1

∴ P(1) is true.

Step 2:

Let us assume that for some k ∈ N, P(k) is true,

i.e., 1.2 + 2.3 + 3.4 + ... + k(k + 1) = "k"/3("k" + 1)("k" + 2)  ...(1)

Step 3:

To prove that P(k + 1) is true,

i.e., to prove that

1.2 + 2.3 + 3.4 + ..... + k(k + 1) +(k + 1)(k + 2) = (("k" + 1))/3("k" + 2)("k" + 3)

Now, L.H.S. = 1.2 + 2.3 + 3.4 + ... + k(k + 1) + (k + 1)(k + 2)

= "k"/3("k" + 1)("k" + 2) + ("k" + 1)("k" + 2)  ...[By (1)]

= ("k" + 1)("k" + 2)("k"/3 + 1)

= (("k" + 1)("k" + 2)("k" + 3))/3

= R.H.S.

∴ P(k + 1) is true.

Step 4:

From all the above steps and by the principle of mathematical induction, the result P(n) is true for all n ∈ N,

i.e., 1.2 + 2.3 + 3.4 + ..... + n(n + 1) = "n"/3 ("n" + 1)("n" + 2), for all n ∈ N.

Concept: Principle of Mathematical Induction
Is there an error in this question or solution?

#### APPEARS IN

Balbharati Mathematics and Statistics 2 (Arts and Science) 11th Standard Maharashtra State Board
Chapter 4 Methods of Induction and Binomial Theorem
Exercise 4.1 | Q 6 | Page 73